2011
DOI: 10.1016/j.jcrysgro.2011.09.003
|View full text |Cite
|
Sign up to set email alerts
|

The influence of N2/H2 and ammonia N source materials on optical and structural properties of AlN films grown by plasma enhanced atomic layer deposition

Abstract: a b s t r a c tThe influence of N 2 /H 2 and ammonia as N source materials on the properties of AlN films grown by plasma enhanced atomic layer deposition using trimethylaluminum as metal source has been studied.The $-2Y grazing-incidence X-ray diffraction, high resolution transmission electron microscopy, and spectroscopic ellipsometry results on AlN films grown using either NH 3 or N 2 /H 2 plasma revealed polycrystalline and wurtzite AlN layers. The AlN growth rate per cycle was decreased from 0.84 to 0.54Å… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
30
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 55 publications
(36 citation statements)
references
References 26 publications
3
30
0
Order By: Relevance
“…11 More recently, plasmaenhanced atomic layer deposition (PEALD) has been demonstrated as an alternative method for AlN deposition. [12][13][14][15][16][17][18][19][20][21][22] The AlN process is also available for thermal ALD but in that case the source material selection is limited and above 400 C deposition temperatures are required. 15 In contrast, the attractive properties of PEALD films include low temperature processing (typically below 300 C), thus increasing the choice of precursors and materials, enabling tunable material properties, and still allowing the typical ALD thickness control below 1 nm accuracy.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…11 More recently, plasmaenhanced atomic layer deposition (PEALD) has been demonstrated as an alternative method for AlN deposition. [12][13][14][15][16][17][18][19][20][21][22] The AlN process is also available for thermal ALD but in that case the source material selection is limited and above 400 C deposition temperatures are required. 15 In contrast, the attractive properties of PEALD films include low temperature processing (typically below 300 C), thus increasing the choice of precursors and materials, enabling tunable material properties, and still allowing the typical ALD thickness control below 1 nm accuracy.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, such conclusion made by Alevli et al based on their x-ray photoelectron spectroscopy and FTIR analysis about their PEALD AlN is questionable. 13 A broad FTIR valley ranging from 2280 to 2060 cm À1 and having the center around 2135 cm À1 is present in the samples from the as-deposited to the samples annealed at 800 C. This mode can be attributed to (NN) vibrations of the Al-N 2 complex. 28,49 The FTIR valleys exhibit a clear shift to higher wavenumbers and broadening as the annealing temperature increases.…”
mentioning
confidence: 96%
See 1 more Smart Citation
“…Therefore we lowered the deposition temperatures by activating NH 3 or N 2 /H 2 through remote plasma and deposited polycrystalline wurtzite AlN thin films at temperatures ranging from 100-500 °C (10)(11)(12). Deposition parameters were optimized for these processes to achieve true ALD conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Although thermal ALD (or atomic layer epitaxy, ALE) of III-nitride thin films, especially AlN, using various types of group-III precursors has been the focus of interest in the 1990s, current trend in the field of III-nitride ALD research is directed towards UV-, hot-wire-or plasmaassisted processes using metalorganic precursors [1][2][3][4][5][6][7][8][9][10][11]. Recently, we showed that ALD-grown III-nitride thin films may suffer from plasma-related oxygen contamination depending on the choice of N-containing plasma gas (N 2 , N 2 /H 2 or NH 3 ) [12,13].…”
mentioning
confidence: 99%